Constructing an identity as a reader and writer at University: a study of journals of Letras first-year students - Birgin, Jimena (Revista Chilena de Pedagogía, 2020)
This paper presents findings based on the analysis of first-year students’ journals at Licenciatura en Letras and Profesorado en Lengua y Literatura of UNRN (Argentine) with the aim to explore the configuration of the literacy practices of the students, as well as the identities shaped by them. First, we consider the potential of using journals written by the students as a methodological tool for data collection and research. Then, based on analytical categories emerging from the journals, we outline the ways in which subjects view their own literacy practices as university students, as well as the ways they see themselves as readers and writers within their disciplinary field.